Nomenclatural Studies Toward a World List of Diptera Genus-Group Names Part VII: Johann Wilhelm Meigen - Evenhuis, Neal L.; Pape, Thomas (Zootaxa, 2019)
The Diptera genus-group names of Johann Wilhelm Meigen are reviewed, revised, and annotated. A total of 266 available genus-group names in 69 families of Diptera are listed alphabetically, including authorship, year and page of the original publication, originally included species, type species and method of fixation, current status of the name, family placement, and any emendations that have been found in the literature. Unavailable names suppressed by ICZN rulings as well as incorrect original and subsequent spellings are included as unnumbered entries. Remarks are given to clarify nomenclatural or taxonomic information. In addition, an index to all the species-group names of Diptera proposed by Meigen (3,117 in total, of which 2,966 are available) is given with a bibliographic reference to each original citation. An appendix gives a complete bibliography of all the known published writings by Meigen, non-zoological as well as zoological.                The following type species designation is proposed: Dasypogon priscus Meigen, 1820 for Podoctria Meigen, 1820, by present designation [Asilidae].                First Reviser actions for multiple original spellings that have not previously been recognized (viz., those made via ICZN Code Art. 24.2.4) or are made herein are given for the following: Chrysotus Meigen, 1824 [Dolichopodidae]; Ocydromia Meigen, 1820 [Hybotidae]; Rhamphomyia Meigen, 1822 [Empididae]; Tachypeza Meigen, 1830a [Hybotidae].                Earlier valid subsequent type-species designations have been found for the following: Ascia Meigen, 1822 [Syrphidae]; Borborus Meigen, 1803 [Sphaeroceridae]; Brachygaster Meigen, 1826 [Sepsidae]; Cephalia Meigen, 1826 [Ulidiidae]; Chrysotus Meigen, 1824 [Dolichopodidae]; Ctenophora Meigen, 1803 [Tipulidae]; Diastata Meigen, 1830a [Diastatidae]; Doros Meigen, 1803 [Syrphidae]; Erioptera Meigen, 1803 [Limoniidae]; Glochina Meigen, 1830a [Limoniidae]; Macrocera Meigen, 1803 [Keroplatidae]; Merodon Meigen, 1803 [Syrphidae]; Mesembrina Meigen, 1826 [Muscidae]; Mycetobia Meigen, 1818a [Anisopodidae]; Odontomyia Meigen, 1803 [Stratiomyidae]; Oedalea Meigen, 1820 [Hybotidae]; Phania Meigen, 1824 [Tachinidae]; Platypeza Meigen, 1803 [Platypezidae]; Platyptera Meigen, 1803 [Empididae]; Platyura Meigen, 1803 [Keroplatidae]; Spilomyia Meigen, 1803 [Syrphidae]; Stegana Meigen, 1830a [Drosophilidae]; Trineura Meigen, 1803 [Phoridae]; Ulidia Meigen, 1826 [Ulidiidae]; Xysta Meigen, 1824 [Tachinidae].                The following type species are fixed herein under ICZN Code Article 70.3.2: Rhagio ibis Fabricius, 1775 for Atherix Meigen, 1803 [Athericidae]; Coelopa pilipes Haliday, 1838 for Coelopa Meigen, 1803 [Coelopidae]; Diastata vagans Loew, 1864 for Diastata Meigen, 1803 [Diastatidae]; Tanypus punctipennis Meigen, 1818a for Tanypus Meigen, 1803 [Chironomidae]. Corrected or clarified nomenclatural status, included species, and/or corrected or clarified type-species are given for: Acrocera Meigen, 1803 [Acroceridae]; Aedes Meigen, 1818a [Culicidae]; Anisomera Meigen, 1818a [Limoniidae]; Ascia Meigen, 1822 [Syrphidae]; Atherix Meigen, 1803 [Athericidae]; Bactria Meigen, 1820 [Asilidae]; Bolitophila Meigen, 1818a [Bolitophilidae]; Borborus Meigen, 1803 [Chloropidae]; Brachygaster Meigen, 1826 [Sepsidae]; Cephalia Meigen, 1826 [Ulidiidae]; Chlorops Meigen, 1803 [Chloropidae]; Chrysotoxum Meigen, 1803 [Syrphidae]; Chrysotus Meigen, 1824 [Dolichopodidae]; Coelopa Meigen, 1830a [Coelopidae]; Ctenophora Meigen, 1803 [Tipulidae]; Dialyta Meigen, 1826 [Muscidae]; Diastata Meigen, 1830a [Diastatidae]; Dictya Meigen, 1803 [Sciomyzidae]; Diomyza Meigen, 1818a [Cecidomyiidae]; Doros Meigen, 1803 [Syrphidae]; Dorycera Meigen, 1830a [Ulidiidae]; Erioptera Meigen, 1803 [Limoniidae]; Furcomyia Meigen, 1818a [Limoniidae]; Glochina Meigen, 1830a [Limoniidae]; Hexacantha Meigen, 1803 [Stratiomyidae]; Hexatoma Meigen, 1818a [Tabanidae]; Lasiops Meigen, 1838 [Muscidae]; Leptina Meigen, 1822 [Tipulidae]; Leptocera Meigen, 1818a [Bolitophilidae]; Leucopis Meigen, 1830a, [Chamaemyiidae]; Loxocera Meigen, 1803 [Psilidae]; Macrocera Meigen, 1803 [Keroplatidae]; Marginomyia Meigen, 1818a [Limoniidae]; Merodon Meigen, 1803 [Syrphidae]; Mesembrina Meigen, 1826 [Muscidae]; Mima Meigen, 1820 [Bombyliidae]; Mycetobia Meigen, 1818a [Anisopodidae]; Nematocera Meigen, 1818a [Limoniidae]; Nodutis Meigen, 1820 [Athericidae]; Odontomyia Meigen, 1803 [Stratiomyidae]; Oedalea Meigen, 1820 [Hybotidae]; Pelecocera Meigen, 1822 [Syrphidae]; Phalangus Meigen, 1822 [Syrphidae]; Phania Meigen, 1824 [Tachinidae]; Platypeza Meigen, 1803 [Platypezidae]; Platyptera Meigen, 1803 [Empididae]; Platyura Meigen, 1803 [Keroplatidae]; Podoctria Meigen, 1820 [Asilidae]; Psilopus Meigen, 1824 [Dolichopodidae]; Sarcophaga Meigen, 1824 [Sarcophagidae]; Stegana Meigen, 1830a [Drosophilidae]; Subula Meigen, 1820 [Xylomyidae]; Tanyglossa Meigen, 1803 [Tabanidae]; Tanypus Meigen, 1803 [Chironomidae]; Therina Meigen, 1830a [Heleomyzidae]; Trineura Meigen, 1803 [Phoridae]; Ulidia Meigen, 1826 [Ulidiidae]; Unomyia Meigen, 1818a [Limoniidae]; Xylota Meigen, 1822 [Syrphidae]; Xysta Meigen, 1824 [Tachinidae].                New synonymies are proposed for the following genus-group names: Melanopangonius Szilády, 1923 under Tanyglossa Meigen, 1803, n. syn. [Tabanidae]; Planuria Meigen, 1826 under Homalura Meigen, 1826, n. syn. [Chloropidae]; Polimera Meigen, 1826 under Polymera Wiedemann, 1820, n. syn. [Limoniidae]; Trepidaria Swinderen, 1822 under Seioptera Kirby & Spence, 1817, n. syn. [Ulidiidae].                Reversal of precedence (Code Article 23.9.2) is invoked in two instances to promote stability in nomenclature. One for homonymy: Sarcophaga Meigen, 1824, nomen protectum [in Sarcophagidae] and Sarcophaga Swinderen, 1822, nomen oblitum [in Calliphoridae]; and one for objective synonymy: Calliphora Robineau-Desvoidy, 1830, nomen protectum and Sarcophaga Swinderen, 1822, nomen oblitum [in Calliphoridae].